2015
DOI: 10.1016/j.nbd.2014.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 cysteine-113 oxidation inhibits its catalytic activity and cellular function in Alzheimer's disease

Abstract: The unique proline isomerase Pin1 is pivotal for protecting against age-dependent neurodegeneration in Alzheimer’s disease (AD), with its inhibition providing a molecular link between tangle and plaque pathologies. Pin1 is oxidatively modified in human AD brains, but little is known about its regulatory mechanisms and pathological significance of such Pin1 modification. In this paper, our determination of crystal structures of oxidized Pin1 reveals a series of Pin1 oxidative modifications on Cys113 in a sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 76 publications
(133 reference statements)
4
85
0
Order By: Relevance
“…Pin1 is also intricately involved in many stages of the cell cycle through direct contact with target proteins as well as indirect action through the regulation of important kinases and phosphatases (Keeney et al 2012;Driver and Lu 2010;Lin et al 2015). We recently reported that the active site Cys-113 residue is oxidatively modified to sulfonic acid in AD brain, and we posit that this modification may account for the decreased Pin1 activity we have observed in AD brain (Chen et al 2015;Sultana et al 2006a, b, c).…”
Section: Signaling Structure and Neurotransmissionmentioning
confidence: 55%
“…Pin1 is also intricately involved in many stages of the cell cycle through direct contact with target proteins as well as indirect action through the regulation of important kinases and phosphatases (Keeney et al 2012;Driver and Lu 2010;Lin et al 2015). We recently reported that the active site Cys-113 residue is oxidatively modified to sulfonic acid in AD brain, and we posit that this modification may account for the decreased Pin1 activity we have observed in AD brain (Chen et al 2015;Sultana et al 2006a, b, c).…”
Section: Signaling Structure and Neurotransmissionmentioning
confidence: 55%
“…These data suggested that Pin1 was somehow inactivated in AD lysates. Pin1 can be oxidized at Cys 113 , blocking activity (9) or inhibited by outside-in glutamatergic signaling (10). To identify the mechanism, we utilized mouse synaptoneurosomes, a highly enriched preparation of pre- and post-synaptic neuronal connections from brain.…”
Section: Resultsmentioning
confidence: 99%
“…The isomerase activity of Pin1 is lost due to oxidation of Cys 113 , a critical amino acid within its active site (9). Whether alterations in inside-out signaling, especially at synaptic sites, can affect Pin1 activity or steady-state protein amounts during AD evolution is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These modifications are likely due to elevated oxidative stress and are involved in various cellular pathways, such as glycolysis, calcium homeostasis, and vesicle transport [12,14,15]. More recently, Cys113 oxidation of proline isomerase, Pin1, in postmortem AD brain has been associated with catalytic inactivity of Pin1 [16].…”
Section: Introductionmentioning
confidence: 99%